Impact of COVID-19 for people living and working with ADHD: A brief review of the literature - Jack Hollingdale; Nicoletta Adamo; Kevin Tierney (AIMS Press, 2021)
Objective: COVID-19 lockdowns have changed the social and environmental context. Those with ADHD are more vulnerable to experiencing difficulties than their non-ADHD peers. This paper attempts to provide a brief summary of the literature that has emerged during the COVID-19 pandemic. Method: A literature search was completed using the following databases; Embase, Ovid Medline, APA PsycInfo. A total of 36 papers were identified as relevant to the topic. Results: The pandemic has exacerbated the core symptoms of ADHD and co-occurring difficulties. Services have adapted their assessment and intervention protocols for tele-health working and findings suggest that tele-interventions present a viable alternative. However, much of this research utilises small sample sizes and a restricted number of population groups. Conclusions: More research is required to determine the effectiveness of ADHD care during the pandemic and whether adaptations will be retained post-pandemic.